(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article examines the origins, evolution, and issues of succession regarding bird imagery within the heraldry of Uzbek statehood and its reflection in modern state symbols, based on a historical-comparative analysis. Utilizing archaeological and written sources, it substantiates that the image of the bird in Turko-Tengrist cosmology symbolized political legitimacy and divine authority. The article reveals the unbroken succession in the heraldry of the Ghaznavids, Seljuks, Timurids, and Uzbek khanates, and scientifically grounds the reliance of the Humo bird on the modern emblem of the Republic of Uzbekistan on ancient statehood traditions.